Understanding local area networks - Jenkins, Neil; Schatt, Stanley (Indianapolis, Indiana : Sams Publishing, 1995)
Shows readers how LANs and their various hardware and software components actually work, helping network administrators decide whether or not LAN is a viable option.
Includes index.
Keywords: LOCAL AREA NETWORKS (COMPUTER NETWORKS)